USING EXPOSITORY TO IMPROVE LISTENING SKILL - Arif Ma'mun Rifa'i (Institut Agama Islam Ngawi, 2013)
USING EXPOSITORY TO IMPROVE LISTENING SKILL Arif Ma’mun RifaiDepartment of Shari>ah, The College for Islamic Studies Ngawi (STAI Ngawi)AbstractTeacher of any grade should have a special teaching media in teaching English listening. In this occasion, the writer tried to make frame of Using expository method with the title above. To achieve the objectives of the study, the writer conducted an experimental research. This research need two groups, they are experimental group and control group. The population of the research was the Eighth Grade Students of MTs Islamiyah Widodaren Ngawi in the Academic Year 2011/2012. The technique that is used random sampling by lottery and the sample of the study was class VIIIA as experimental group and class VIIID as a control group. Each group consisted of 20 students’ in class VIIIA as an experimental group and 20 students’ in class VIIID as control group. The students’ in experiment group was given treatment and control group was not given treatment. The instrument used for collecting the data was listening test that was gained from the analysis result of used tests. The data was obtained from the pre – test and post – test scores of the both group. Based on the statistical analysis, it could be seen that the mean of post – test scores of experiment group was higher than the mean post – test scores of the control group. To know whether the differences of the two mean was significant or not, t test formula was applied. The result of computation in control group was 0.66 and for the experiment group was 0.81. So, here, it indicates of variable X and variable Y in control group had average correlation. While it indicates of variable X and variable Y in experiment group had strong correlation. The critical value of t for the tailed level of significant in which 5% and degree of freedom (df) 20 was 0.44. Since the obtained value was higher than the critical value of t, it meant the difference between the mean of both group was significant. Keywords: Teaching, Expository, Listening skill.